Ultrafast gas chromatographic method for quantitative determination of total FAMEs in biodiesel: An analysis of 90 s - Tercini, Antonio Carlos Bergamaschi [UNESP]; Pinesi, Murilo [UNESP]; Cyntia Calera, Gabrielle [UNESP]; Sequinel, Rodrigo [UNESP]; Hatanaka, Rafael Rodrigues [UNESP]; de Oliveira, José Eduardo [UNESP]; Flumignan, Danilo Luiz [UNESP] (Elsevier, 2018)
Several physicochemical parameters must be determined in order to verify the quality of commercial biodiesel, and the analysis of total fatty acid methyl esters (FAMEs) is the main parameter. Therefore, an efficient and alternative analytical method using gas chromatography coupled with ultrafast module is important. This method was developed to quantify FAMEs in biodiesel commercial samples that originated from different feedstock (babaçu, coconut, rapeseed, corn, soybean, animal/palm oil and sunflower). The chromatographic run time is 90 s. When compared with the official methods, we had a much faster one, which provided an analytical frequency of up to 205 samples a day. This analytical method has been validated according to in-house validation parameters, such as linearity, repeatability, reproducibility (intermediate precision) and accuracy. Two analytical curves were prepared, one for determinate long carbon chain FAMEs (C16–C24) and another for short carbon chain FAMEs (C6–C14). The coefficient of determination (which represents the percentage of the data that is closest to the line of best fit) was 0.9992 for the C18 curve (long chain) and the C12 curve (short chain). Repeatability and reproducibility presented a relative standard deviation of 0.75% and 1.68% for the C18 curve and 0.44% and 1.05% for the C12 curve, respectively. The accuracy had a standard error of 0.2 for soybean biodiesel, 0.4 for animal/palm commercial biodiesel and 0.2 for babaçu biodiesel.
Keywords: Biodiesel; FAMEs; Quality control; Ultrafast gas chromatography